Chemoprevention or mastectomy for women at high risk of developing breast cancer. Issue 3 (November 2015) - Sismondi, Piero; D'Alonzo, Marta; Pecchio, Silvia; Bounous, Valentina Elisabetta; Robba, Elisabetta; Biglia, Nicoletta
Highlights: It is important to identify high risk breast cancer women, this patients should receive individualized counseling to establish the best risk reduction strategy. Great efforts have been made in search of cancer preventive strategies such as chemoprevention therapy and risk-reduction surgery. Risk-reduction agents are recommended for high risk breast cancer women aged ≥35 years old, Tamoxifen is presently deemed to be the preventive agent of choice in most high-risk women. Estrogen receptor negative tumors, remain a challenge for prevention. Bilateral risk-reducing mastectomy decreases the risk of developing breast cancer by approximately 90% in moderate- and high-risk women and in known BRCA1/2 mutation carriers. Abstract: Breast cancer (BC) is the most commonly diagnosed invasive cancer among women; in developed countries, BC occurs in one out of eight women during her lifetime. Many factors, both genetic and non-genetic, determine a woman's risk of breast cancer and several mathematical models have been proposed that determine the risk. It is important to identify those at high risk, as there are now effective preventive strategies, such as chemoprevention therapy and risk-reduction surgery. Risk-reduction agents are recommended for women aged 35 years or more who are at high risk of breast cancer. Tamoxifen is presently deemed to be the agent of choice. However, raloxifene may be preferable, at least for some postmenopausal women, because of its lack of effect on the endometrium and the reduced incidence of venous thromboembolic events compared with tamoxifen. Prophylactic surgery has been widely investigated. Bilateral mastectomy decreases the risk of developing breast cancer by approximately 90% in women at moderate or high risk and in known BRCA1/2 mutation carriers. This review summarizes the recent advances in the identification of women at high risk of developing breast cancer and reports on the strategies used to prevent breast cancer; the risk–benefit balance of such preventive choices is also briefly analyzed.